(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The objective of this study was to see the association of the prognosis of ischemic stroke patients with or without collateralization after carotid stenosis. This study was conducted on 36 patients presenting with acute ischemic stroke who were going through digital subtraction angiography from March 2017 to March 2018. Collateralization status after unilateral or bilateral stenosis was evaluated. Modified ranking scale (mRS) score was measured on the first day of the stroke and after three months. The disability of ischemic stroke patients was compared between patients who developed collateralization and who had not. Among them, 61.6% developed collateralization. Among the patients who developed collateralization after three months, 90.9% patients had mRS scale of ≤2 and who not developed collateralization, 85.7% patients had mRS scale of ≤2. In both the groups, the p value was <0.05. It can be concluded that carotid stenosed patients who suffered from ischemic stroke, most of the patients disability improved to some extents whether collateralization developed or not among the major vessels.